Tafsir Nusantara in the Science Field: A Bibliometric Analysis in 2011-2022 Using Scopus Database - Noor, Faiq Makhdum; Asriyadin, Asriyadin (Program Studi Ilmu Al-Qur`an dan Tafsir, Fakultas Ushuluddin, UIN Sunan Kudus, 2023)
Tafsir Nusantara in the Science Field: A Bibliometric Analysis in 2011-2022 Using Scopus Database. The study of tafsir nusantara is a cultural product that was born from the dialectical process between the mufassir and the cultural reality. This research aims to analyze the study of tafsir nusantara in the science field using bibliometric techniques from 2011-2022. This research was conducted on August 25, 2022. The data obtained were 16 documents taken from the Scopus database with the keyword